KIMYO FANINI OʻQITISH JARAYONINI TAKOMILLASHTIRISHDA SUN’IY INTELLEKTDAN FOYDALANISHNING AHAMIYATI - Xasanova, X.N. (SCIENCE and SOCIETY, 2025)
This article analyzes the issues of improving chemistry lessons using the capabilities of artificial intelligence. The role was considered .artificial intelligence in teaching chemistry in improving independent thinking, creativity and research activities, consolidating and making certain scientific conclusions based on them.